2016
DOI: 10.1161/hypertensionaha.115.06186
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Specific Steroid Profiles Associated With Aldosterone-Producing Adenomas

Abstract: P rimary aldosteronism (PA) is the leading cause of secondary hypertension with a prevalence of 4.3% in the general hypertensive population and 9.5% of patients referred to hypertension units. 1 The diagnosis of PA is fundamental because these patients are at an increased risk of cardiovascular and cerebrovascular complications and metabolic syndrome compared with patients with primary hypertension and similar cardiovascular risk profiles. [2][3][4][5] The underlying cause of PA in the majority of patients is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 31 publications
7
90
0
2
Order By: Relevance
“…Although we could not establish similar utility in the present study, we could confirm 8.5-fold higher peripheral venous plasma concentrations of 18-oxocortisol in patients with APAs than BAH, a finding also consistent with earlier studies (25,26,37 ). We have also established elsewhere that increases in plasma 18-oxocortisol among patients with APAs are particularly prominent and largely confined to tumors with somatic KCNJ5 (potassium channel, inwardly rectifying subfamily J, member 5) mutations (39 ). In earlier work, Gordon et al established that increases of 18-oxocortisol are largely confined to patients with angiotensin-unresponsive APAs (38 ).…”
Section: Discussionsupporting
confidence: 81%
“…Although we could not establish similar utility in the present study, we could confirm 8.5-fold higher peripheral venous plasma concentrations of 18-oxocortisol in patients with APAs than BAH, a finding also consistent with earlier studies (25,26,37 ). We have also established elsewhere that increases in plasma 18-oxocortisol among patients with APAs are particularly prominent and largely confined to tumors with somatic KCNJ5 (potassium channel, inwardly rectifying subfamily J, member 5) mutations (39 ). In earlier work, Gordon et al established that increases of 18-oxocortisol are largely confined to patients with angiotensin-unresponsive APAs (38 ).…”
Section: Discussionsupporting
confidence: 81%
“…[16][17][18][19][20] An interesting novel approach consists of the measurement of a selected steroid profile by mass spectrometry. 21,22 Nevertheless, additional diagnostic steps will be needed to localize potential APA.…”
Section: Hypertensionmentioning
confidence: 99%
“…These results indicate that the peripheral level of 18oxoF, which is significantly affected by APA secretion, can be a clinically useful biomarker not only to differentiate APA from BHA but also to avoid unnecessary surgery for non-functioning adrenocortical nodules concurrent with hyperplasia or microadenoma . However, Williams et al (2016) demonstrated that the 18oxoF concentration in APA cases with KCNJ5 mutations was 18-and 16-fold higher in lateralized adrenal veins and peripheral vein plasma, respectively, compared with that in APA cases with other mutations (ATP1A1, ATP2B3, and CACNA1D). The cause of the upregulation of 18oxoF synthesis in APA cases remains unclear.…”
Section: The Clinical Significance Of Cyp11b2mentioning
confidence: 88%